2017
DOI: 10.1371/journal.pone.0176472
|View full text |Cite
|
Sign up to set email alerts
|

In vitro induction of NETosis: Comprehensive live imaging comparison and systematic review

Abstract: BackgroundMultiple inducers of in vitro Neutrophil Extracellular Trap (NET) formation (NETosis) have been described. Since there is much variation in study design and results, our aim was to create a systematic review of NETosis inducers and perform a standardized in vitro study of NETosis inducers important in (cardiac) wound healing.MethodsIn vitro NETosis was studied by incubating neutrophils with PMA, living and dead bacteria (S. aureus and E. coli), LPS, (activated) platelets (supernatant), glucose and ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
142
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 157 publications
(156 citation statements)
references
References 216 publications
5
142
0
1
Order By: Relevance
“…Kenny et al, 2017). A comprehensive review of these pathways has been published recently (Hoppenbrouwers et al, 2017) and is beyond the scope of this review. However, pathways relevant to comparative discussions will be highlighted in later sections.…”
Section: Rets and Nets Are Traps Involved In Biological Defencementioning
confidence: 99%
“…Kenny et al, 2017). A comprehensive review of these pathways has been published recently (Hoppenbrouwers et al, 2017) and is beyond the scope of this review. However, pathways relevant to comparative discussions will be highlighted in later sections.…”
Section: Rets and Nets Are Traps Involved In Biological Defencementioning
confidence: 99%
“…In light of these previous results, we investigated whether NETs may contribute to increased epithelial permeability in CRS. 45 Therefore, NETs can mediate inflammatory responses by increasing the neutrophil migration through the increase of the endothelial cells surface expression of ICAM-1 in CRS.NETs formation is triggered by different physiological and nonphysiological compounds 46. Therefore, the present study suggests that NETs may have beneficial effects on the epithelial permeability, possibly contributing to the maintenance of epithelial integrity.…”
mentioning
confidence: 65%
“…NETs formation is triggered by different physiological and nonphysiological compounds. 46 It is also suggested that antibiotics could be non-physiological compounds that influence NETs release.…”
Section: Discussionmentioning
confidence: 99%
“…21,22 NETosis stimulated via the PKC stimulator, PMA leads to phosphorylation of PKC, p38 MAPKs, and ERK1/2. 23,24 However, no stimulation of these kinases was detected in the reaction to anti-β2GPI/β2GPI. Zn 2+ is crucial for NETosis triggered via PMA.…”
Section: Discussionmentioning
confidence: 95%
“…Although numerous studies have identified reactions linked with NET delivery, the understanding of the reactions inside cells that participate in NET generation is insufficient regarding the various NET stimulators.Although numerous candidate targets of anti-β 2 GPI/β 2 GPI have been identified in signal pathways to cause NETosis, most promising mechanisms were shown to be irrelevant to NETosis. NETosis stimulated via the PKC stimulator, PMA leads to phosphorylation of PKC, p38 MAPKs, and ERK1/2 23,24. NETosis stimulated via the PKC stimulator, PMA leads to phosphorylation of PKC, p38 MAPKs, and ERK1/2 23,24.…”
mentioning
confidence: 99%